Kinetics of superoxide scavenging by glutathione: an evaluation of its role in the removal of mitochondrial superoxide. (1st December 2003) - Jones, C.M.; Lawrence, A.; Wardman, P.; Burkitt, M.J.
Abstract : Superoxide radicals are produced in trace amounts by the mitochondrial respiratory chain. Most are removed rapidly by superoxide dismutase in the matrix. Superoxide is also known to react with glutathione. Reported values of the rate constant for this reaction range from 10 2 to in excess of 10 5 M −1 ·s −1 . The magnitude of this rate constant has important physiological implications because, if it is at the upper end of the reported range, a significant proportion of mitochondrial superoxide will evade removal by superoxide dismutase, and will oxidize glutathione to the potentially harmful glutathionyl radical. Using EPR spectroscopy to monitor competition between glutathione and the spin trap 5, 5-dimethyl-1-pyrroline N -oxide for reaction with superoxide, we have estimated that the rate constant for the reaction between superoxide and glutathione is only 200 M −1 ·s −1 . Hence superoxide dismutase will always out-compete glutathione for reaction with the superoxide radical, thereby preventing formation of the glutathionyl radical.